MEMBANGUN RASA EMPATI DALAM KEGIATAN P5 DENGAN TEMA "KITA SEMUA BERSAUDARA" DI TK KEMALA BHAYANGKARI 05 KOTA SERANG - Kusumawadhani, Dina; Auliya, Ghina; Shofa, Luthfiyah Robbiyati (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2025)
This study aims to increase students' sense of empathy through P5 activities under the slogan “We are all brothers” at Kemala Bhayangkari Kindergarten 05 Serang City. This activity aims to develop students' competencies and personalities based on Pancasila values. The five most important profiles developed through P5 are; loyalty, piety, diversity, mutual cooperation, independence, critical thinking and creativity. This research uses a qualitative approach that includes data collection techniques through interviews, observation and documentation. Research findings show that P5 activities can increase students' feelings of empathy through sharing and donating habits. Kemala Bhaygkari 05 Kindergarten teachers reflect, plan, implement and complete K5 activities to increase students' empathy. All our students, teachers and parents are participating in this event to raise money to be distributed to orphans in the region.